Investigation and management of pancreatic tumours. Issue 2 (11th October 2013) - Smith, Lyn A; Jamieson, Nigel B; McKay, Colin J
Abstract : Pancreatic cancer is the 10th most commonly diagnosed cancer in the UK and the fifth most common cause of cancer death. It remains one of the most aggressive cancers with over 95% of patients affected dying of their disease. Often presenting at an advanced stage of disease progression, there is currently no simple screening test available. Therefore a high clinical suspicion and prompt appropriate investigation is required from physicians when dealing with patients with symptoms in keeping with pancreatic cancer. The gastroenterology 2010 curriculum states that trainees should learn the presentation and multidisciplinary management of patients with pancreatic tumours. In this article we discuss the typical clinical presentations of common and less common pancreatic tumours followed by the investigation, staging and management required.